Pengaruh Image Branding Duta Baca Provinsi Sulawesi Selatan Terhadap Minat Kunjung Pemustaka di Dinas Perpustakaan dan Kearsipan Provinsi Sulawesi Selatan - Khaerunnisa; Irvan Mulyadi; Marni (UPT Perpustakaan UIN Alauddin Makassar, 2022)
Abstract This study aims to determine whether there is an influence of reading ambassador's branding image on the interest of visiting users and how much influence the reading ambassador's branding image has on the interest of visiting users at the Library and Archives Service of South Sulawesi Province. This study uses causal associative research located at the Library and Archives Service of South Sulawesi Province. The sampling technique used the Slovin formula so that the sample in this study was 98 respondents. The data obtained using a questionnaire and data processing techniques in this study using the help of SPSS version 23. The results in this study indicate the branding image of the ambassador because it has a strong influence on the interest of visitors to visit the Library and Archives Service by 42.3%. The significant level of the reading ambassador branding image variable is 0.000, which is smaller than 0.01 which means that it is accepted and then rejected, thus library promotion with the reading ambassador's branding image has an effect on increasing user interest in visiting. So this study shows that the branding image of the reading ambassador will have an impact on increasing the interest of visiting users